Evaluation of chemopreventive and chemotherapeutic effect of Artemisia vulgaris extract against diethylnitrosamine induced hepatocellular carcinogenesis in Balb C mice - Ali,S. (2020)
Abstract The main objective of current study was to investigate the chemopreventive and chemotherapeutic activity of Artemisia vulgaris extract on diethylnitrosoamine induced hepatocarcinogenesis in Balb C mice. Diethylnitrosoamine (DEN: 0.9%) was prepared to induce hepatocarcinoma in Balb C mice. The extract Artemisia vulgaris (AV) was prepared by maceration technique. Mice were classified into four groups as follows: Group 1 a control group (N=7) received saline solution (3.5 μl/mg), group 2 (N=14) received diethylnitrosoamine (3.5 μl/mg) intraperitoneally once in a week for eight consecutive weeks, group 3 (N=7) received only plant extract (AV: 150 mg/kg (Body weight) once in a week, while group 4 (N=7) was given in combination of diethylnitrosoamine (3.5 μl/mg) and plant extract (AV: 150 mg/kg (body weight). After eight weeks of DEN administration, mice of group 2 were divided into two subgroups containing seven mice each; subgroup 1 was sacrificed while subgroup 2 was treated with plant extract only (150 mg/kg (body weight)) once in a week for eight consecutive weeks. The DEN injected mice significant decline in levels of albumin with concomitant significant elevations such as aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, alpha feto protein, gamma glutamyl transferase, 5 nucleotidase, glucose-6-phosphate dehydrogenase and bilirubin. The administration of A. vulgaris significantly decreased the DEN induced hepatotoxicity. Present study revealed the potential anti-cancerous nature of Artemisia vulgaris, both in case of chemopreventive and post-treatment of A. vulgaris. Further studies are needed to explore the mechanism of prevention and therapy.